FROM JUSTICE TO EQUITY IN HEALTH - Costa Gomes, Carlos (2024)
Justice is approached as equity as a path to equality. Starting from Aristotle, who was perhaps the one who best defined the concept of justice as equity; dialoguing with Rawls, whose perspective of justice aims not to result in the interest of all, or of the majority, but as a fundamental duty to understand collective needs, without, however, failing to bring into this dialogue Amartya Sem, who states that justice as equity resides in capabilities and in the freedom of each person to choose, among the possible paths, the one that best meets their own needs. As a way of responding to the objective of this study, which aims to highlight equity as a support for equal access to health, it was decided to use the exploratory bibliographic research method on reference authors on the topic under analysis. It was concluded that, of the different needs, access to health care is fundamental to ensuring a person's rights. From the point of view of bioethics and the right to health (biolaw), justice as equity (and not so much equality) is that which can best facilitate access to health care and services, since people are different and therefore have specific needs; In Portugal, a national strategy is necessary, which cannot and should not remain hostage to ideological policies, but rather involves all health sectors, including the private sector, to respond to needs and promote equitable access.